Pelatihan Parental Acceptance untuk Meningkatkan Penerimaan Orang Tua dengan Anak Disabilitas Intelektual - Feti Pratiwi; Yudi Kurniawan; Markus Nanang Irawan Budi Susilo (Institut Teknologi dan Bisnis Semarang, 2025)
Children with intellectual disabilities face challenges in their cognitive and adaptive abilities within their environment. This condition clearly sets them apart from their peers without disabilities. Parents need to understand and accept all forms of limitations their child may have so they can provide proper care and nurturing, enabling optimal growth and development. However, not all parents are able to comprehend and accept their child's condition. This is why training activities are necessary for these parents. Training is provided to parents of children with intellectual disabilities at SDLB-C1 (moderately intellectually disabled) SLB Widya Bhakti Semarang. The training employs methods of lecturing and simulation through floortime activities. Through this training, each participant gains new knowledge and skills as an effort to increase parental acceptance towards children with intellectual disabilities.